The Composition of the Biography in the English Literature - Surghi, Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2020)
What is the purpose of every biography? Tell a life? Pursue a form that accounts for an experience? Distinguish the singular that enables a movement of dissolution of life to structure it under a form of work? Some of these questions guide the present work, which proposes a journey through various moments of the English biography (Aubrey, Boswell, Johnson, Strachey) in which the search for a biographical method coincides with the definition of a singularity: intelligence literary that fascinates and seduces the biographer.